Endocrine Outcome and Quality of Life After Transsphenoidal Resection of Pituitary Adenoma—A Prospective Randomized Single-Blinded Study Comparing Endoscopic Versus Microscopic Resection - Andrej Pala; Nadja Grübel; Benjamin Mayer; Ralf Becker; Fabian Sommer; Bernd Schmitz; Gwendolin Etzrodt-Walter; Christian Rainer Wirtz; Michal Hlavac (Neurology International)
Background: Endoscopic pituitary surgery might yield better endocrine outcomes compared to microscopic resection. We conducted a prospective, randomized, single-blinded study to compare the endocrine outcome and quality of life (QoL) of patients with newly diagnosed pituitary adenoma who underwent either endoscopic or microscopic transsphenoidal surgery (NCT03515603). Methods: Due to slow recruitment, this study had to be stopped prematurely. Out of 170 transsphenoidal pituitary surgeries performed during the study period, 36 patients were enrolled in this study. The primary endpoint was based on the development of a new hypopituitarism. Secondary endpoints included the extent of resection, complications, and QoL. Results: Endoscopic surgery was performed in 47.2% (n = 17). A new hypopituitarism was found in 8.3% (n = 3). All these cases underwent microscopic resection. Arginine vasopressin deficiency was found in 2.7% (n = 1) after microscopic resection. Gross total resection was achieved in 94.4% (n = 34). No surgical complications or new neurological deficits were observed. QoL improved significantly after the surgery, as measured by EQ-VAS (p = 0.003). According to EQ-5D3L, QoL improved or remained unchanged in almost all patients. No significant difference was found in QoL between the endoscopic and microscopic groups. Conclusion: The endoscopic technique appears to offer benefits in the treatment of pituitary adenomas, particularly in terms of achieving a favorable endocrine outcome.